A robot joint dynamic cable using self-repairing polyurethane material and preparation method thereof
By using self-healing polyurethane materials and modified nanomaterials, the problem of easy damage to traditional cables under dynamic loads is solved, and high mechanical strength, thermal stability and self-healing capabilities are achieved, which are suitable for dynamic cables of robot joints.
Patent Information
- Application Number
- CN202411834756.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-13
AI Technical Summary
Traditional cables are prone to fatigue and damage when frequently bent, twisted and rubbed in robot joints and automated production lines, resulting in conductor breakage and damage to the insulation layer, affecting signal transmission quality and equipment stability.
Self-healing polyurethane material is used to construct a soft and hard segment structure by reacting polytetrahydrofuran glycol with hexamethylene diisocyanate. 1,4-butanediol and dopamine hydrochloride are added to form a hydrogen bond network, and combined with modified carbon nanotubes, montmorillonite and boron nitride are enhanced to improve the mechanical strength, thermal stability and self-healing ability of the material.
It significantly improves the tensile resistance, fatigue resistance, electrical properties and heat dissipation properties of the material, and can operate stably for a long time in complex environments, extending the service life of the cable.
Smart Images

Figure CN119320552B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to a robot joint dynamic cable made of self-repairing polyurethane material and a preparation method thereof. Background Art
[0002] Existing conventional cables play a vital role in modern electronic devices, robots and mechanical systems, mainly for the transmission of power and signals. These cables are usually composed of conductors and insulation materials, and are designed to meet basic electrical and mechanical performance requirements. With the rapid development of science and technology, especially in the fields of smart devices, automation and robotics, the performance requirements of traditional cables are also constantly increasing.
[0003] Although traditional conductor materials have excellent conductivity, they face many challenges in dynamic applications. Conventional cables are prone to fatigue and damage under frequent bending, twisting and friction, especially in high-mobility application scenarios. For example, in robot joints and automated production lines, cables must withstand continuous dynamic loads and complex motion trajectories. This mechanical fatigue not only causes conductor breakage, but may also cause damage to the insulation layer, thereby affecting the signal transmission quality and the overall stability of the equipment. In addition, as the equipment's requirements for signal transmission speed and accuracy increase, any slight cable damage may cause system failure, resulting in reduced production efficiency and economic losses; secondly, conventional cables are relatively lacking in performance in high and low temperature environments. Many traditional materials are prone to aging, embrittlement, and even cracking under extreme temperature conditions, which in turn affects the safety and reliability of the cables. Summary of the invention
[0004] In view of the above problems, the object of the present invention is to provide a robot joint dynamic cable using self-healing polyurethane material and a preparation method thereof. First, the soft and hard segment structure of polyurethane is constructed by reacting polytetrahydrofuran diol with hexamethylene diisocyanate, and 1,4-butanediol is added to extend the chain and dopamine hydrochloride is introduced to enhance the hard segment structure and form a self-healing hydrogen bond network, so that the material has excellent mechanical strength, thermal stability and self-healing ability. Secondly, modified carbon nanotubes are introduced by plasma treatment and silane coupling agent composite modified carbon nanotubes, which significantly improves the tensile strength, fatigue resistance and electrical properties of the material. Montmorillonite is composite modified by organic treatment and polyethyleneimine to improve the crack resistance and wear resistance of the material. After surface modification, the dispersibility and thermal conductivity of boron nitride are enhanced, thereby providing the material with excellent heat dissipation performance and dimensional stability. The synergistic effect between the components makes the composite material perform well in mechanical properties, electrical properties, heat dissipation and wear resistance, and is particularly suitable for robot dynamic cables, and can operate stably for a long time in complex environments.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a robot joint dynamic cable using a self-repairing polyurethane material, the method for preparing a robot joint dynamic cable using a self-repairing polyurethane material comprising:
[0007] S1: After vacuum drying, polytetrahydrofuran diol is added to a reactor, and hexamethylene diisocyanate is added, and the reaction is carried out under nitrogen protection to obtain a reaction solution A; after cooling, 1,4-butanediol and dopamine hydrochloride are added to obtain a reaction solution B, and after heating, the reaction is carried out to obtain a reaction solution C; after adding dibutyltin dilaurate, the reaction is continued and vacuum degassing is carried out, and after completion, the product is purified to obtain a modified polyurethane;
[0008] S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas for plasma treatment to obtain first modified carbon nanotubes, dispersing the first modified carbon nanotubes in anhydrous ethanol, adding a silane coupling agent KH550, refluxing after ultrasonic treatment, filtering, washing with ethanol, and vacuum drying to obtain modified carbon nanotubes;
[0009] S3: dispersing montmorillonite in deionized water and stirring to obtain a montmorillonite dispersion, adding octadecyltrimethylammonium bromide solution dropwise, continuing stirring, then adding polyethyleneimine solution to obtain a reaction solution D, performing ultrasonic treatment and stirring again, and finally centrifuging, washing and freeze-drying to obtain a modified montmorillonite;
[0010] S4: dispersing boron nitride in toluene to obtain a boron nitride dispersion, adding glacial acetic acid to adjust the pH after ultrasonic dispersion, and then adding 3-glycidyloxypropyltrimethoxysilane to obtain a reaction solution E, and refluxing under nitrogen protection; collecting by centrifugation, washing with anhydrous ethanol, and vacuum drying to obtain a first modified boron nitride; dispersing the first modified boron nitride in Tris buffer and adding dopamine hydrochloride, stirring at room temperature; centrifuging, washing, and freeze-drying to obtain a modified boron nitride;
[0011] S5: Place the modified polyurethane in an internal mixer, add an antioxidant, a dispersant and a toughening agent, add modified carbon nanotubes, modified montmorillonite and modified boron nitride in sequence after internal mixing to obtain a mixed material, and obtain a composite material after constant temperature mixing. Inject the composite material into a single-screw extruder, and simultaneously feed the conductor body to coat the composite material on the surface of the conductor. After cooling, obtain a robot joint dynamic cable using a self-healing polyurethane material.
[0012] As a preferred technical scheme of the present invention, in step S1, the temperature of the polytetrahydrofuran diol vacuum drying is 85-95°C, for example, can be 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, but is not limited to the enumerated numerical value, and other unenumerated numerical values within this numerical range are equally applicable.
[0013] In some optional embodiments, the time of described polytetrahydrofuran diol vacuum drying is 3-4h, for example, can be 3h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4h, but is not limited to enumerated numerical value, and other unenumerated numerical values in this numerical range are equally applicable.
[0014] In some optional embodiments, the molar ratio of the polytetrahydrofuran diol to hexamethylene diisocyanate is 0.35-0.45:1, for example, it can be 0.35:1, 0.36:1, 0.37:1, 0.38:1, 0.39:1, 0.40:1, 0.41:1, 0.42:1, 0.43:1, 0.44:1 or 0.45:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0015] In some optional embodiments, the temperature of the reaction under nitrogen protection is 85-95°C, for example, it can be 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0016] In some optional embodiments, the reaction time under nitrogen protection is 1.5-2.5h, for example, it can be 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2.0h, 2.1h, 2.2h, 2.3h, 2.4h or 2.5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] In some optional embodiments, the reaction liquid A is cooled to 55-65°C, for example, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In some optional embodiments, the molar ratio of the 1,4-butanediol to the dopamine hydrochloride modified diamine is 0.8-1.2:1, for example, it can be 0.8:1, 0.84:1, 0.88:1, 0.92:1, 0.96:1, 1.0:1, 1.04:1, 1.08:1, 1.12:1, 1.16:1 or 1.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] In some optional embodiments, the molar ratio of the total amount of dopamine hydrochloride modified diamine to hexamethylene diisocyanate is 0.25-0.35:1, for example, it can be 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, 0.30:1, 0.31:1, 0.32:1, 0.33:1, 0.34:1 or 0.35:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] In some optional embodiments, the temperature of the heating reaction of the reaction liquid B is 105-115°C, for example, it can be 105°C, 106°C, 107°C, 108°C, 109°C, 110°C, 111°C, 112°C, 113°C, 114°C or 115°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In some optional embodiments, the heating reaction time of the reaction liquid B is 3.5-4.5h, for example, it can be 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h or 4.5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] In some optional embodiments, the feeding amount of dibutyltin dilaurate is 0.08-0.12wt.% of the reaction liquid C, for example, it can be 0.08wt.%, 0.085wt.%, 0.09wt.%, 0.095wt.%, 0.10wt.%, 0.105wt.%, 0.11wt.%, 0.115wt.% or 0.12wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] In some optional embodiments, the dibutyltin dilaurate is added and the reaction is continued for 30-40 minutes, for example, 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional embodiments, the vacuum degassing time is 15-25 min, for example, it can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] As a preferred technical solution of the present invention, in step S2, the gas for plasma treatment is an Ar / O2 mixed gas in which the volume ratio of argon and oxygen is 3:1-5:1, for example, it can be 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.8:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional embodiments, the power of the plasma treatment is 75-85 W, for example, it can be 75 W, 76 W, 77 W, 78 W, 79 W, 80 W, 81 W, 82 W, 83 W, 84 W or 85 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In some optional embodiments, the plasma treatment time is 3-5 min, for example, it can be 3 min, 3.2 min, 3.4 min, 3.6 min, 3.8 min, 4 min, 4.2 min, 4.4 min, 4.6 min, 4.8 min or 5 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In some optional embodiments, the mass fraction of the first modified carbon nanotubes dispersed in anhydrous ethanol is 2-3wt.%, for example, it can be 2wt.%, 2.1wt.%, 2.2wt.%, 2.3wt.%, 2.4wt.%, 2.5wt.%, 2.6wt.%, 2.7wt.%, 2.8wt.%, 2.9wt.% or 3wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] In some optional embodiments, the added amount of the silane coupling agent KH550 is 15-25% of the mass of the carbon nanotubes, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In some optional embodiments, the ultrasonic treatment time is 25-35 min, for example, it can be 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In some optional embodiments, the reflux temperature is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional embodiments, the reflux time is 3.5-4.5h, for example, it can be 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h or 4.5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In some optional embodiments, the vacuum drying temperature is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In some optional embodiments, the vacuum drying time is 10-14h, for example, it can be 10h, 10.4h, 10.8h, 11.2h, 11.6h, 12h, 12.4h, 12.8h, 13.2h, 13.6h or 14h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] As a preferred technical solution of the present invention, in step S3, the mass fraction of the montmorillonite dispersed in deionized water is 2.5-3.5wt.%, for example, it can be 2.5wt.%, 2.6wt.%, 2.7wt.%, 2.8wt.%, 2.9wt.%, 3.0wt.%, 3.1wt.%, 3.2wt.%, 3.3wt.%, 3.4wt.% or 3.5wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional embodiments, the stirring temperature after the montmorillonite is dispersed in deionized water is 25-35°C, for example, it can be 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C or 35°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the stirring time after the montmorillonite is dispersed in deionized water is 10-20 minutes, for example, it can be 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes or 20 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In some optional embodiments, the mass fraction of the octadecyltrimethylammonium bromide solution is 4-6wt.%, for example, it can be 4wt.%, 4.2wt.%, 4.4wt.%, 4.6wt.%, 4.8wt.%, 5.0wt.%, 5.2wt.%, 5.4wt.%, 5.6wt.%, 5.8wt.% or 6wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In some optional embodiments, the amount of octadecyltrimethylammonium bromide solution added is 25-35% of the mass of montmorillonite, for example, it can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional embodiments, the continued stirring time is 3.5-4.5h, for example, it can be 3.5h, 3.6h, 3.7h, 3.8h, 3.9h, 4.0h, 4.1h, 4.2h, 4.3h, 4.4h or 4.5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In some optional embodiments, the added amount of polyethyleneimine is 15-25% of the mass of montmorillonite, for example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% or 25%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In some optional embodiments, the mass fraction of the polyethyleneimine solution is 1.5-2.5wt.%, for example, it can be 1.5wt.%, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.%, 2.0wt.%, 2.1wt.%, 2.2wt.%, 2.3wt.%, 2.4wt.% or 2.5wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional embodiments, the power of the ultrasonic treatment of the reaction liquid D is 250-350 W, for example, it can be 250 W, 260 W, 270 W, 280 W, 290 W, 300 W, 310 W, 320 W, 330 W, 340 W or 350 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In some optional embodiments, the ultrasonic treatment time of the reaction liquid D is 25-35 min, for example, it can be 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some optional embodiments, the temperature of the reaction liquid D after ultrasound and stirring is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional embodiments, the stirring time of the reaction liquid D after ultrasound is 5.5-6.5h, for example, it can be 5.5h, 5.6h, 5.7h, 5.8h, 5.9h, 6.0h, 6.1h, 6.2h, 6.3h, 6.4h or 6.5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional embodiments, the freeze-drying time is 20-28h, for example, it can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h or 28h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, in step S4, the mass fraction of the boron nitride in toluene is 3.5-4.5wt.%, for example, it can be 3.5wt.%, 3.6wt.%, 3.7wt.%, 3.8wt.%, 3.9wt.%, 4.0wt.%, 4.1wt.%, 4.2wt.%, 4.3wt.%, 4.4wt.% or 4.5wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In some optional embodiments, the ultrasonic dispersion time of the boron nitride dispersion is 15-20 min, for example, it can be 15.0 min, 15.5 min, 16.0 min, 16.5 min, 17.0 min, 17.5 min, 18.0 min, 18.5 min, 19.0 min or 19.5 min or 20.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In some optional embodiments, the pH is adjusted to 4-5 using glacial acetic acid, for example, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In some optional embodiments, the feeding amount of the 3-glycidyloxypropyltrimethoxysilane is 12-18% of the mass of the boron nitride, for example, it can be 12.0%, 12.6%, 13.2%, 13.8%, 14.4%, 15.0%, 15.6%, 16.2%, 16.8%, 17.4% or 18.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In some optional embodiments, the reflux temperature of the reaction liquid E under nitrogen protection is 70-80°C, for example, it can be 70.0°C, 71.0°C, 72.0°C, 73.0°C, 74.0°C, 75.0°C, 76.0°C, 77.0°C, 78.0°C, 79.0°C or 80.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional embodiments, the reflux time of the reaction liquid E under nitrogen protection is 6-8h, for example, it can be 6.0h, 6.2h, 6.4h, 6.6h, 6.8h, 7.0h, 7.2h, 7.4h, 7.6h, 7.8h or 8.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional embodiments, the vacuum drying temperature is 60-70°C, for example, it can be 60.0°C, 61.0°C, 62.0°C, 63.0°C, 64.0°C, 65.0°C, 66.0°C, 67.0°C, 68.0°C, 69.0°C or 70.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional embodiments, the vacuum drying time is 8-12 h, for example, it can be 8.0 h, 8.4 h, 8.8 h, 9.2 h, 9.6 h, 10.0 h, 10.4 h, 10.8 h, 11.2 h, 11.6 h or 12.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional embodiments, the pH value of the Tris buffer is 8.3-8.7, for example, it can be 8.3, 8.4, 8.5, 8.6, 8.7, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional embodiments, the mass fraction of the first modified boron nitride in the buffer solution is 3.0-4.0wt.%, for example, it can be 3.0wt.%, 3.1wt.%, 3.2wt.%, 3.3wt.%, 3.4wt.%, 3.5wt.%, 3.6wt.%, 3.7wt.%, 3.8wt.%, 3.9wt.% or 4.0wt.%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional embodiments, the addition amount of dopamine hydrochloride is 10-15% of the mass of the first modified boron nitride, for example, it can be 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5% or 15.0%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional embodiments, the room temperature stirring time is 20-24h, for example, it can be 20.0h, 20.5h, 21.0h, 21.5h, 22.0h, 22.5h, 23.0h, 23.5h or 24.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional embodiments, the freeze-drying time is 18-24 hours, for example, it can be 18.0h, 18.5h, 19.0h, 19.5h, 20.0h, 20.5h, 21.0h, 21.5h, 22.0h, 22.5h, 23.0h, 23.5h or 24.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] As a preferred technical solution of the present invention, in step S5, the kneading temperature is 180-190°C, for example, it can be 180.0°C, 181.0°C, 182.0°C, 183.0°C, 184.0°C, 185.0°C, 186.0°C, 187.0°C, 188.0°C, 189.0°C or 190.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional embodiments, the kneading time is 8-12 min, for example, it can be 8.0 min, 8.4 min, 8.8 min, 9.2 min, 9.6 min, 10.0 min, 10.4 min, 10.8 min, 11.2 min, 11.6 min or 12.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional embodiments, the temperature of the constant temperature mixing of the mixed material is 190-200°C, for example, it can be 190.0°C, 191.0°C, 192.0°C, 193.0°C, 194.0°C, 195.0°C, 196.0°C, 197.0°C, 198.0°C, 199.0°C or 200.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional embodiments, the rotation speed of the constant temperature mixing of the mixed material is 65-75rpm, for example, it can be 65.0rpm, 66.0rpm, 67.0rpm, 68.0rpm, 69.0rpm, 70.0rpm, 71.0rpm, 72.0rpm, 73.0rpm, 74.0rpm or 75.0rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In some optional embodiments, the constant temperature mixing time of the mixed material is 10-20 min, for example, it can be 10.0 min, 11.0 min, 12.0 min, 13.0 min, 14.0 min, 15.0 min, 16.0 min, 17.0 min, 18.0 min, 19.0 min or 20.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] In some optional embodiments, the temperature of the single-screw extruder barrel is 185-195°C, for example, it can be 185.0°C, 186.0°C, 187.0°C, 188.0°C, 189.0°C, 190.0°C, 191.0°C, 192.0°C, 193.0°C, 194.0°C or 195.0°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] As a preferred technical solution of the present invention, the robot joint dynamic cable made of self-repairing polyurethane material comprises the following components in parts by weight:
[0068] Modified polyurethane 65-75 parts;
[0069] 3-5 parts of modified carbon nanotubes;
[0070] 8-12 parts of modified montmorillonite;
[0071] 12-15 parts of modified boron nitride;
[0072] Antioxidant 0.3-0.5 parts;
[0073] Dispersant 0.8-1.2 parts;
[0074] 2-3 parts of toughening agent.
[0075] In some optional examples, the mass parts of the modified polyurethane are 65-75 parts, for example, it can be 65 parts, 66 parts, 67 parts, 68 parts, 69 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts or 75 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some optional examples, the mass proportion of modified carbon nanotubes is 3-5 parts, for example, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts or 5 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] In some optional examples, the mass proportion of modified montmorillonite is 8-12 parts, for example, it can be 8 parts, 8.4 parts, 8.8 parts, 9.2 parts, 9.6 parts, 10 parts, 10.4 parts, 10.8 parts, 11.2 parts, 11.6 parts or 12 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] In some optional examples, the mass fraction of modified boron nitride is 12-15 parts, for example, it can be 12 parts, 12.2 parts, 12.4 parts, 12.6 parts, 12.8 parts, 13 parts, 13.2 parts, 13.4 parts, 13.6 parts, 13.8 parts, 14 parts, 14.2 parts, 14.4 parts, 14.6 parts, 14.8 parts or 15 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] In some optional examples, the mass fraction of the antioxidant is 0.3-0.5 parts, for example, it can be 0.3 parts, 0.32 parts, 0.34 parts, 0.36 parts, 0.38 parts, 0.40 parts, 0.42 parts, 0.44 parts, 0.46 parts, 0.48 parts or 0.5 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] In some optional examples, the mass fraction of the dispersant is 0.8-1.2 parts, for example, it can be 0.8 parts, 0.84 parts, 0.88 parts, 0.92 parts, 0.96 parts, 1.0 parts, 1.04 parts, 1.08 parts, 1.12 parts, 1.16 parts or 1.2 parts, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In some optional examples, the mass fraction of the toughening agent is 2-3 parts, for example, it can be 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3.0 parts, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0082] In a second aspect, the present invention provides a highly weather-resistant solvent-free coating.
[0083] In the present invention, the basic network structure of polyurethane is formed by reacting polytetrahydrofuran diol with hexamethylene diisocyanate. As a flexible soft segment, polytetrahydrofuran diol provides excellent elasticity and flexibility, so that it can effectively absorb mechanical stress under repeated bending and torsion conditions, while the rigid structure of hexamethylene diisocyanate forms a hard segment, giving the material a certain mechanical strength and thermal stability. Subsequently, 1,4-butanediol is added as a chain extender by cooling, and its terminal hydroxyl group reacts with the isocyanate group in the prepolymer to extend the molecular chain length and increase the molecular weight. At the same time, the introduction of dopamine hydrochloride further enhances the hard segment structure by reacting its amino group with hexamethylene diisocyanate to generate a urea bond, and its phenolic hydroxyl group provides a dynamic cross-linking network through an intermolecular and intramolecular hydrogen bond network, so that the material has self-repairing properties when it is subjected to microcracks or damage. Finally, a dibutyltin dilaurate catalyst is added to accelerate the reaction, and volatile byproducts that may be generated in the reaction are removed by vacuum degassing, thereby obtaining a modified polyurethane.
[0084] The synergistic effect of the soft and hard segments of the modified polyurethane enables it to exhibit excellent performance in dynamic environments. The mechanical strength and high-temperature stability given to the material by the hard segment are combined with the flexibility and low-temperature toughness of the soft segment, making the material perform well in a wide temperature range. The dynamic hydrogen bond network enables the material to have self-healing ability, and it can repair damage by breaking and reorganizing hydrogen bonds when microcracks occur, thereby extending the service life of the cable. In addition, the phenolic hydroxyl groups in the dopamine hydrochloride molecules also provide active binding sites for subsequent fillers, ensuring the uniform dispersion of the fillers and the interfacial bonding strength, thereby further improving the overall performance of the composite material.
[0085] The present invention introduces carbon nanotubes as fillers and modifies them. Carbon nanotubes are treated with plasma of Ar / O2 mixed gas to introduce polar groups such as carboxyl and hydroxyl groups on their surfaces. This treatment significantly improves the surface chemical activity of the carbon nanotubes, reduces their tendency to agglomerate, and improves their dispersibility in the polyurethane matrix. Subsequently, the carbon nanotubes are further functionalized using a silane coupling agent KH550. The trimethoxysilane group in the silane coupling agent KH550 undergoes a condensation reaction with the hydroxyl or carboxyl group on the surface of the carbon nanotube to form a stable Si-OC bond; the amino group at the end of the molecular chain of the silane coupling agent KH550 further provides more active sites for hydrogen bonding or chemical bonding with the polyurethane matrix. This dual modification process ensures the surface functionalization of the carbon nanotubes and the interfacial bonding strength with the polyurethane matrix.
[0086] The role of modified carbon nanotubes in composite materials is not only reflected in their high strength and high modulus forming a stress transfer network in the matrix, significantly improving the tensile strength and fatigue resistance of the composite materials, but also in their conductivity forming a conductive network in the matrix, thereby giving the cable good electrical properties.
[0087] The present invention introduces montmorillonite as a filler and modifies it. Through the organic treatment of octadecyl trimethyl ammonium bromide, the sodium ions between the layers are replaced with long-chain organic cations to complete the interlayer ion exchange reaction. The introduction of long-chain quaternary ammonium salts greatly increases the interlayer spacing of montmorillonite, and the surface is converted from hydrophilic to organophilic, thereby improving its stripping efficiency and dispersibility in organic solvents. Subsequently, a polyethyleneimine solution is added, and the amino groups in the polyethyleneimine can further interact with montmorillonite through electrostatic action to form a stable organic-inorganic composite material, and more active sites are provided for the combination with a polyurethane matrix.
[0088] Modified montmorillonite provides excellent crack resistance and wear resistance in composite materials through its layered structure. The two-dimensional layers effectively prevent the propagation of microcracks and disperse stress under dynamic bending and torsion conditions, thereby improving the material's fatigue resistance.
[0089] The present invention introduces modified boron nitride as a filler. After the boron nitride is modified by 3-glycidyloxypropyltrimethoxysilane, epoxy groups are introduced on the surface of the boron nitride, further enhancing its chemical activity and the interfacial bonding force with the polyurethane matrix. Subsequently, a layer of polyhydrochloride dopamine coating is formed on the surface of the boron nitride through the self-polymerization of dopamine hydrochloride, and the phenolic hydroxyl group and amino group in the polyhydrochloride dopamine further enhance the dispersibility and surface activity of the boron nitride. The modified boron nitride can not only be evenly distributed in the matrix, but also provide efficient heat dissipation capacity for the composite material through its high thermal conductivity.
[0090] The role of modified boron nitride in composite materials is mainly reflected in the improvement of high and low temperature resistance and wear resistance. Its two-dimensional sheet structure can build a heat conduction network in the matrix, significantly reduce the thermal expansion coefficient of the material, and ensure the dimensional stability of the material under high temperature conditions; at the same time, the rigid sheet of boron nitride at low temperature can improve the brittle resistance of the material. In addition, the sheet structure of boron nitride can resist surface damage under dynamic mechanical loads, significantly improving the wear resistance of composite materials.
[0091] At the same time, there is a synergistic enhancement effect between the components: modified polyurethane as a matrix material forms a close interface with carbon nanotubes, montmorillonite and boron nitride, significantly improving the overall performance of the composite material. The high strength and conductivity of carbon nanotubes and the high thermal conductivity of boron nitride form an electro-thermal synergistic enhancement effect, which makes the cable have excellent conductivity and heat dissipation performance. The two-dimensional layered structure of montmorillonite forms a multi-scale reinforcement network through the staggered distribution of carbon nanotubes, which further improves the crack resistance and fatigue resistance of the composite material. In addition, the sheet structure of boron nitride enhances the wear resistance and high and low temperature resistance of the composite material, while the carbon nanotubes and dopamine hydrochloride construct a self-healing interface through a dynamic hydrogen bond network, ensuring the sustainable use performance of the material. The synergistic dispersion between fillers and the dynamic cross-linking network of the matrix work together to make the final cable show excellent mechanical properties, durability and functionality, meeting the use requirements of robot dynamic cables in complex environments.
[0092] Compared with the prior art, the present invention has the following beneficial effects:
[0093] (1) The soft and hard segment structures of polyurethane are formed by the reaction of polytetramethylene diisocyanate and hexamethylene diisocyanate. 1,4-Butanediol is added as a chain extender to extend the molecular chain and increase the molecular weight. The introduction of dopamine hydrochloride strengthens the hard segment structure. Its phenolic hydroxyl groups form a dynamic cross-linking network through hydrogen bonds, giving the material self-healing ability. Under the synergistic effect of the soft and rigid segments, the modified polyurethane has excellent mechanical strength, thermal stability, flexibility, low-temperature toughness, and self-healing ability, extending the life of the material.
[0094] (2) Carbon nanotubes are introduced and modified by plasma treatment and silane coupling agent. The modified carbon nanotubes form a stress transfer network in the matrix through their high strength and high modulus, significantly improving the tensile strength and fatigue resistance. In addition, the conductive network is formed through conductivity, so that the cable has good electrical properties.
[0095] (3) Montmorillonite is introduced and treated with octadecyltrimethylammonium bromide for organic treatment. At the same time, polyethyleneimine is introduced to form a stable organic-inorganic composite material with montmorillonite. Its layered structure provides anti-cracking and wear resistance in the composite material, effectively disperses stress under dynamic bending and torsion conditions, and improves fatigue resistance.
[0096] (4) The surface of boron nitride was modified by 3-glycidyloxypropyltrimethoxysilane to introduce epoxy groups and enhance its chemical activity. Then, dopamine hydrochloride was used for self-polymerization to form a polydopamine hydrochloride coating on the surface of boron nitride, which improved its dispersibility and surface activity. The high thermal conductivity of the modified boron nitride provides excellent heat dissipation capacity for the composite material. Its two-dimensional sheet structure can effectively construct a heat conduction network, reduce the thermal expansion coefficient of the material, and ensure the dimensional stability of the material at high temperatures. Its rigid sheet layer improves the material's resistance to brittleness and enhances its wear resistance.
[0097] (5) Modified polyurethane is used as a matrix material to form a close interface with carbon nanotubes, montmorillonite and boron nitride, significantly improving the overall performance of the composite material; the high strength and conductivity of carbon nanotubes and the high thermal conductivity of boron nitride form a synergistic effect, giving the cable excellent electrical conductivity and heat dissipation performance; the two-dimensional layered structure of montmorillonite and the staggered distribution of carbon nanotubes form a multi-scale reinforcement network, which improves the material's resistance to cracking and fatigue resistance; the dynamic hydrogen bond network between carbon nanotubes and dopamine hydrochloride realizes self-healing effect, ensuring the long-term sustainable use of the material; the synergistic effect between different components makes the final composite material show excellent performance in mechanical properties, durability, functionality and other aspects, meeting the use requirements of robot dynamic cables in complex environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0098] Figure 1 A flow chart of a method for preparing a robot joint dynamic cable using a self-healing polyurethane material provided in Example 1 of the present invention;
[0099] Figure 2 This is a scanning electron microscope image of a robot joint dynamic cable made of self-healing polyurethane material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0100] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0101] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:
[0102] Polytetrahydrofurandiol: purchased from Hangzhou Sanlong New Materials Co., Ltd.
[0103] Hexamethylene diisocyanate: purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.
[0104] 1,4-Butanediol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0105] Dopamine hydrochloride: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0106] Dibutyltin dilaurate: purchased from Changde Kairui Chemical Technology Co., Ltd.;
[0107] Carbon nanotubes: purchased from Jiangsu Tiannai Technology Co., Ltd.
[0108] Anhydrous ethanol: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0109] Silane coupling agent KH550: purchased from Nanjing Herun Coupling Agent Co., Ltd.
[0110] Montmorillonite: purchased from Ningcheng Xiangxi Chemical Co., Ltd.
[0111] Octadecyltrimethylammonium bromide: purchased from Wuhan Aikang Chemicals Co., Ltd.
[0112] Polyethyleneimine: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0113] Boron nitride: purchased from Henan Nitrogen Boron New Material Technology Co., Ltd.;
[0114] Toluene: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0115] Glacial acetic acid: purchased from Jining Bocheng Chemical Co., Ltd.
[0116] 3-Glycidyloxypropyltrimethoxysilane: purchased from Nanjing Herun Coupling Agent Co., Ltd.;
[0117] Tris buffer: purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0118] Antioxidant 1010: purchased from Tianjin Lianlong New Materials Co., Ltd.
[0119] Antioxidant 1076: purchased from Tianjin Lianlong New Materials Co., Ltd.;
[0120] Antioxidant 245: purchased from Tianjin Lianlong New Materials Co., Ltd.
[0121] DISPERBYK-2150: purchased from BYK Chemicals;
[0122] BYK-9077: purchased from BYK Chemicals;
[0123] Kraton G1651: purchased from Kraton;
[0124] Kraton FG1901: purchased from Kraton;
[0125] Example 1
[0126] like Figure 1 As shown, this embodiment provides a robot joint dynamic cable using a self-healing polyurethane material and a preparation method thereof, wherein the robot joint dynamic cable using a self-healing polyurethane material comprises the following components in parts by weight:
[0127] Modified polyurethane 70 parts;
[0128] 4.5 parts of modified carbon nanotubes;
[0129] 10.8 parts of modified montmorillonite;
[0130] 14 parts of modified boron nitride;
[0131] Antioxidant 0.42 parts;
[0132] 1.16 parts of dispersant;
[0133] 2.8 parts of toughening agent.
[0134] The preparation method specifically comprises the following steps:
[0135] S1: After vacuum drying polytetrahydrofuran diol at 90° C. for 3.5 hours, add it into a reactor, and add hexamethylene diisocyanate, wherein the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 0.4:1, and react at 89° C. for 2 hours under nitrogen protection to obtain reaction solution A; after cooling to 55° C., add 1,4-butanediol and dopamine hydrochloride to obtain reaction solution B, wherein the molar ratio of 1,4-butanediol to dopamine hydrochloride is 1:1; the molar ratio of dopamine hydrochloride to hexamethylene diisocyanate is 0.32:1, and heat to 110° C. and react for 4 hours to obtain reaction solution C; after adding dibutyltin dilaurate in an amount of 0.11wt.% of the reaction solution C, continue to react for 35 minutes, vacuum degas for 20 minutes, and end to purchase a purified product to obtain a modified polyurethane;
[0136] S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas with a volume ratio of 3:1, and performing plasma treatment for 5 minutes at a processing power of 78W to obtain a first modified carbon nanotube, dispersing the first modified carbon nanotube in anhydrous ethanol at a mass fraction of 3wt.%, adding a silane coupling agent KH550 in an amount of 22% of the mass of the carbon nanotube, and refluxing after ultrasonic treatment for 30 minutes, wherein the reflux temperature is 75°C and the time is 4h, filtering, washing with ethanol, and vacuum drying at 55°C for 12h to obtain the modified carbon nanotube;
[0137] S3: Disperse montmorillonite in deionized water and stir for 15 min at 25°C to obtain a montmorillonite dispersion with a mass fraction of 3.0 wt.%, dropwise add octadecyltrimethylammonium bromide solution with a mass fraction of 5 wt.%, wherein the amount of octadecyltrimethylammonium bromide solution added is 30% of the mass of montmorillonite, continue stirring for 3.5 h, then add 2.5 wt.% polyethyleneimine solution with a mass fraction to obtain a reaction solution D, wherein the amount of polyethyleneimine added is 20% of the mass of montmorillonite, perform ultrasonic treatment and then stir, wherein the ultrasonic power is 300 W, the ultrasonic treatment time is 30 min, the stirring temperature after ultrasonic treatment is 65°C, the time is 6 h, and finally centrifuge, wash and freeze-dry for 25 h to obtain modified montmorillonite;
[0138] S4: Boron nitride is dispersed in toluene to obtain a boron nitride dispersion with a mass fraction of 3.5wt.%, and after ultrasonic dispersion for 15 minutes, glacial acetic acid is added to adjust the pH to 4, and then 3-glycidyloxypropyltrimethoxysilane is added in an amount of 15% of the mass of the boron nitride to obtain a reaction solution E, which is refluxed under nitrogen protection, wherein the reflux temperature is 75°C and the time is 7h; after centrifugation and collection, it is washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain a first modified boron nitride; the first modified boron nitride is dispersed in Tris buffer, wherein the mass fraction of the first modified boron nitride in the buffer is 3.0wt.%, dopamine hydrochloride is added in an amount of 12% of the mass of the first modified boron nitride, and stirred at room temperature for 23h; centrifugation, washing, and freeze-drying for 20h to obtain modified boron nitride;
[0139] S5: Place the modified polyurethane in an internal mixer, add antioxidant 1010, DISPERBYK-2150 and Kraton G1651, and mix at 185°C for 10 minutes, then add modified carbon nanotubes, modified montmorillonite and modified boron nitride in sequence to obtain a mixed material, and obtain a composite material after constant temperature mixing, wherein the constant temperature mixing temperature is 198°C and the time is 15 minutes, and the composite material is injected into a single screw extruder with a barrel temperature of 190°C, and the conductor is fed into it at the same time, and the composite material is coated on the surface of the conductor, and after cooling, a robot joint dynamic cable using self-healing polyurethane material is obtained. Figure 2This is a scanning electron microscope image of the cable. It can be seen that the cable surface is smooth and uniform, the surface structure is dense, the integrity is good, and the repair function has not yet been activated.
[0140] Example 2
[0141] This embodiment provides a robot joint dynamic cable using a self-repairing polyurethane material and a preparation method thereof, wherein the robot joint dynamic cable using a self-repairing polyurethane material comprises the following components in parts by weight:
[0142] Modified polyurethane 65 parts;
[0143] 4.8 parts of modified carbon nanotubes;
[0144] 8 parts of modified montmorillonite;
[0145] 13 parts of modified boron nitride;
[0146] Antioxidant 0.48 parts;
[0147] 0.8 parts of dispersant;
[0148] 3 parts of toughening agent.
[0149] The preparation method specifically comprises the following steps:
[0150] S1: After vacuum drying polytetrahydrofuran diol at 95° C. for 3 hours, add it into a reactor, and add hexamethylene diisocyanate, wherein the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 0.45:1, and react at 95° C. for 1.5 hours under nitrogen protection to obtain reaction solution A; after cooling to 65° C., add 1,4-butanediol and dopamine hydrochloride to obtain reaction solution B, wherein the molar ratio of 1,4-butanediol to dopamine hydrochloride is 1.2:1; the molar ratio of the total amount of dopamine hydrochloride to hexamethylene diisocyanate is 0.25:1, and heat to 115° C. and react for 3.5 hours to obtain reaction solution C; after adding dibutyltin dilaurate in an amount of 0.08wt.% of the reaction solution C, continue to react for 40 minutes and vacuum degas for 15 minutes, and then purchase a purified product to obtain a modified polyurethane;
[0151] S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas with a volume ratio of 4:1, and performing plasma treatment for 3 minutes at a processing power of 75 W to obtain a first modified carbon nanotube, dispersing the first modified carbon nanotube in anhydrous ethanol at a mass fraction of 2.5 wt.%, adding a silane coupling agent KH550 in an amount of 25% of the mass of the carbon nanotube, and refluxing after ultrasonic treatment for 25 minutes, wherein the reflux temperature is 80°C and the time is 4.5 hours, filtering, washing with ethanol, and vacuum drying at 65°C for 10 hours to obtain the modified carbon nanotube;
[0152] S3: Disperse montmorillonite in deionized water and stir for 20 min at 35°C to obtain a montmorillonite dispersion with a mass fraction of 3.5 wt.%, add dropwise a 4 wt.% octadecyltrimethylammonium bromide solution, wherein the amount of octadecyltrimethylammonium bromide solution added is 35% of the mass of montmorillonite, continue stirring for 4 h, then add a 1.5 wt.% polyethyleneimine solution to obtain a reaction solution D, wherein the amount of polyethyleneimine added is 25% of the mass of montmorillonite, perform ultrasonic treatment and then stir, wherein the ultrasonic power is 250 W, the ultrasonic treatment time is 25 min, the stirring temperature after ultrasonic treatment is 75°C, the time is 5.5 h, and finally centrifuge, wash and freeze-dry for 20 h to obtain modified montmorillonite;
[0153] S4: Boron nitride is dispersed in toluene to obtain a boron nitride dispersion with a mass fraction of 4.5wt.%, and after ultrasonic dispersion for 18 minutes, glacial acetic acid is added to adjust the pH to 4.5, and then 3-glycidyloxypropyltrimethoxysilane is added in an amount of 18% of the mass of the boron nitride to obtain a reaction solution E, which is refluxed under nitrogen protection, wherein the reflux temperature is 80°C and the time is 6 hours; after centrifugation and collection, it is washed with anhydrous ethanol, and vacuum dried at 70°C for 8 hours to obtain a first modified boron nitride; the first modified boron nitride is dispersed in Tris buffer, wherein the mass fraction of the first modified boron nitride in the buffer is 3.5wt.%, dopamine hydrochloride is added in an amount of 15% of the mass of the first modified boron nitride, and stirred at room temperature for 20 hours; centrifugation, washing, and freeze-drying for 24 hours to obtain modified boron nitride;
[0154] S5: Place the modified polyurethane in an internal mixer, add antioxidant 1076, BYK-9077 and Kraton FG1901, and mix at 180°C for 8 minutes, then add modified carbon nanotubes, modified montmorillonite and modified boron nitride in sequence to obtain a mixed material, and obtain a composite material after constant temperature mixing, wherein the constant temperature mixing temperature is 195°C and the time is 10 minutes, inject the composite material into a single screw extruder with a barrel temperature of 195°C, and at the same time feed the conductor body to coat the composite material on the surface of the conductor, and after cooling, obtain a robot joint dynamic cable using self-healing polyurethane material.
[0155] Example 3
[0156] This embodiment provides a robot joint dynamic cable using a self-repairing polyurethane material and a preparation method thereof, wherein the robot joint dynamic cable using a self-repairing polyurethane material comprises the following components in parts by weight:
[0157] Modified polyurethane 72 parts;
[0158] 3 parts of modified carbon nanotubes;
[0159] Modified montmorillonite 11.2 parts;
[0160] 12 parts of modified boron nitride;
[0161] 0.3 parts of antioxidant;
[0162] Dispersant 1.0 part;
[0163] 2 parts toughening agent.
[0164] The preparation method specifically comprises the following steps:
[0165] S1: After vacuum drying polytetrahydrofuran diol at 92° C. for 4 hours, add it into a reactor, and add hexamethylene diisocyanate, wherein the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 0.35:1, and react at 85° C. for 2.2 hours under nitrogen protection to obtain reaction solution A; after cooling to 60° C., add 1,4-butanediol and dopamine hydrochloride to obtain reaction solution B, wherein the molar ratio of 1,4-butanediol to dopamine hydrochloride is 1.14:1; the molar ratio of the total amount of dopamine hydrochloride to hexamethylene diisocyanate is 0.35:1, and heat to 105° C. and react for 4.5 hours to obtain reaction solution C; after adding dibutyltin dilaurate in an amount of 0.10wt.% of the reaction solution C, continue to react for 38 minutes and vacuum degas for 25 minutes, and then purchase a purified product to obtain a modified polyurethane;
[0166] S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas with a volume ratio of 5:1, and performing plasma treatment for 4.5 minutes at a processing power of 85 W to obtain a first modified carbon nanotube, dispersing the first modified carbon nanotube in anhydrous ethanol at a mass fraction of 2 wt.%, adding a silane coupling agent KH550 in an amount of 15% of the mass of the carbon nanotube, and refluxing after ultrasonic treatment for 35 minutes, wherein the reflux temperature is 82°C and the time is 3.5 hours, filtering, washing with ethanol, and vacuum drying at 60°C for 14 hours to obtain modified carbon nanotubes;
[0167] S3: Disperse montmorillonite in deionized water and stir for 10 min at 30°C to obtain a montmorillonite dispersion with a mass fraction of 2.5 wt.%, add dropwise a 6 wt.% octadecyltrimethylammonium bromide solution, wherein the amount of octadecyltrimethylammonium bromide solution added is 25% of the mass of montmorillonite, continue stirring for 4.2 h, then add a 2 wt.% polyethyleneimine solution to obtain a reaction solution D, wherein the amount of polyethyleneimine added is 15% of the mass of montmorillonite, perform ultrasonic treatment and then stir, wherein the ultrasonic power is 350 W, the ultrasonic treatment time is 35 min, the temperature after ultrasonic treatment and stirring is 72°C, the time is 6.5 h, and finally centrifuge, wash and freeze-dry for 28 h to obtain modified montmorillonite;
[0168] S4: Boron nitride is dispersed in toluene to obtain a boron nitride dispersion with a mass fraction of 4.2wt.%, and after ultrasonic dispersion for 16 minutes, glacial acetic acid is added to adjust the pH to 4.8, and then 3-glycidyloxypropyltrimethoxysilane is added in an amount of 12% of the mass of the boron nitride to obtain a reaction solution E, which is refluxed under nitrogen protection, wherein the reflux temperature is 70°C and the time is 7.5h; after centrifugation and collection, it is washed with anhydrous ethanol, and vacuum dried at 68°C for 10h to obtain a first modified boron nitride; the first modified boron nitride is dispersed in Tris buffer, wherein the mass fraction of the first modified boron nitride in the buffer is 4.0wt.%, dopamine hydrochloride is added in an amount of 10% of the mass of the first modified boron nitride, and stirred at room temperature for 24h; centrifugation, washing, and freeze-drying for 18h to obtain modified boron nitride;
[0169] S5: Place the modified polyurethane in an internal mixer, add antioxidant 245, DISPERBYK-2150 and Kraton G1651, and mix at 190°C for 12 minutes, then add modified carbon nanotubes, modified montmorillonite and modified boron nitride in sequence to obtain a mixed material, and obtain a composite material after constant temperature mixing, wherein the constant temperature mixing temperature is 190°C and the time is 20 minutes, and the composite material is injected into a single screw extruder with a barrel temperature of 185°C, and the conductor is fed into it at the same time, and the composite material is coated on the surface of the conductor, and after cooling, a robot joint dynamic cable using self-healing polyurethane material is obtained.
[0170] Example 4
[0171] This embodiment provides a robot joint dynamic cable using a self-repairing polyurethane material and a preparation method thereof, wherein the robot joint dynamic cable using a self-repairing polyurethane material comprises the following components in parts by weight:
[0172] Modified polyurethane 75 parts;
[0173] 5 parts of modified carbon nanotubes;
[0174] 12 parts of modified montmorillonite;
[0175] 15 parts of modified boron nitride;
[0176] 0.5 parts of antioxidant;
[0177] 1.2 parts of dispersant;
[0178] 2.5 parts of toughening agent.
[0179] The preparation method specifically comprises the following steps:
[0180] S1: After vacuum drying polytetrahydrofuran diol at 85° C. for 3.8 hours, add it into a reactor, and add hexamethylene diisocyanate, wherein the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 0.42:1, and react at 92° C. for 2.5 hours under nitrogen protection to obtain reaction solution A; after cooling to 62° C., add 1,4-butanediol and dopamine hydrochloride to obtain reaction solution B, wherein the molar ratio of 1,4-butanediol to dopamine hydrochloride is 0.8:1; the molar ratio of the total amount of dopamine hydrochloride to hexamethylene diisocyanate is 0.3:1, and the temperature is raised to 113° C. and reacted for 4.3 hours to obtain reaction solution C; after adding dibutyltin dilaurate in an amount of 0.12wt.% of the reaction solution C, continue to react for 30 minutes and vacuum degas for 22 minutes, and then purchase a purified product to obtain a modified polyurethane;
[0181] S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas with a volume ratio of 3:1, and performing plasma treatment for 4 minutes at a treatment power of 80 W to obtain a first modified carbon nanotube, dispersing the first modified carbon nanotube in anhydrous ethanol at a mass fraction of 2.7 wt.%, adding a silane coupling agent KH550 in an amount of 20% of the mass of the carbon nanotube, and refluxing after ultrasonic treatment for 33 minutes, wherein the reflux temperature is 85°C and the time is 4.3 hours, filtering, washing with ethanol, and vacuum drying at 63°C for 13 hours to obtain modified carbon nanotubes;
[0182] S3: Disperse montmorillonite in deionized water and stir for 18 min at 32°C to obtain a montmorillonite dispersion with a mass fraction of 3.2 wt.%, add dropwise a 5.6 wt.% octadecyltrimethylammonium bromide solution, wherein the amount of octadecyltrimethylammonium bromide solution added is 32% of the mass of montmorillonite, continue stirring for 4.5 h, then add a 2.2 wt.% polyethyleneimine solution to obtain a reaction solution D, wherein the amount of polyethyleneimine added is 23% of the mass of montmorillonite, perform ultrasonic treatment and then stir, wherein the ultrasonic power is 320 W, the ultrasonic treatment time is 33 min, the stirring temperature after ultrasonic treatment is 70°C, the time is 6.3 h, and finally centrifuge, wash and freeze-dry for 27 h to obtain modified montmorillonite;
[0183] S4: Boron nitride is dispersed in toluene to obtain a boron nitride dispersion with a mass fraction of 4.0wt.%, and after ultrasonic dispersion for 20 minutes, glacial acetic acid is added to adjust the pH to 5, and then 3-glycidyloxypropyltrimethoxysilane is added in an amount of 17% of the mass of the boron nitride to obtain a reaction solution E, which is refluxed under nitrogen protection, wherein the reflux temperature is 77°C and the time is 8 hours; after centrifugation and collection, it is washed with anhydrous ethanol, and vacuum dried at 65°C for 11 hours to obtain a first modified boron nitride; the first modified boron nitride is dispersed in Tris buffer, wherein the mass fraction of the first modified boron nitride in the buffer is 3.8wt.%, and dopamine hydrochloride is added in an amount of 13% of the mass of the first modified boron nitride, and stirred at room temperature for 22 hours; centrifugation, washing, and freeze-drying for 22 hours to obtain modified boron nitride;
[0184] S5: Place the modified polyurethane in an internal mixer, add antioxidant 1010, antioxidant 245, BYK-9077 and Kraton FG1901, and mix at 188°C for 11 minutes, then add modified carbon nanotubes, modified montmorillonite and modified boron nitride in sequence to obtain a mixed material, and obtain a composite material after constant temperature mixing, wherein the constant temperature mixing temperature is 200°C and the time is 18 minutes, and the composite material is injected into a single screw extruder with a barrel temperature of 193°C, and the conductor is fed into it at the same time, and the composite material is coated on the surface of the conductor, and after cooling, a robot joint dynamic cable using self-healing polyurethane material is obtained.
[0185] Comparative Example 1
[0186] This comparative example provides a robot joint dynamic cable using a self-healing polyurethane material. The difference from Example 1 is that in step S1, the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 0.2:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0187] Comparative Example 2
[0188] This comparative example provides a robot joint dynamic cable using a self-healing polyurethane material, which differs from Example 1 in that in step S1, the molar ratio of polytetrahydrofuran diol to hexamethylene diisocyanate is 1:1, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0189] Comparative Example 3
[0190] This comparative example provides a robot joint dynamic cable made of self-healing polyurethane material. The difference from Example 1 is that in step S5, the mass fraction of modified carbon nanotubes is 10 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0191] Comparative Example 4
[0192] This comparative example provides a robot joint dynamic cable using a self-healing polyurethane material. The difference from Example 1 is that in step S5, the mass portion of the modified carbon nanotubes is 1 part, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0193] Comparative Example 5
[0194] This comparative example provides a robot joint dynamic cable using a self-healing polyurethane material. The difference from Example 1 is that in step S5, the mass fraction of modified boron nitride is 20 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0195] Comparative Example 6
[0196] This comparative example provides a robot joint dynamic cable using a self-healing polyurethane material. The difference from Example 1 is that in step S5, the mass portion of modified boron nitride is 5 parts, and the other operating steps and process parameters are exactly the same as those in Example 1.
[0197] The performance test of the robot joint dynamic cables using self-healing polyurethane materials in the above Examples 1-4 and Comparative Examples 1-6 was carried out, and the specific process is as follows:
[0198] According to GB / T1040.3-2006, the tensile strength and elongation at break of the test samples were tested;
[0199] 90° bending test: select a 1.5m long sample, strip off 50mm of insulation at both ends, fix the top, leave 20cm in the fixture, and set the bending radius to 6 times the cable diameter. Hang a heavy hammer and connect the conductor, perform 180° reciprocating bending at a frequency of 40 times per minute, and the extreme bending position is 90° with the conductor axis;
[0200] Heat resistance test: Place the sample in an oven, set the temperature to 150°C, heat treat for 1 hour, then take it out and observe whether the sample is deformed.
[0201] The test results are shown in Table 1.
[0202] Table 1: Performance test results of robot joint dynamic cables using self-healing polyurethane materials in Examples 1-4 and Comparative Examples 1-6
[0203]
[0204] It can be seen from Table 1 that the robot joint dynamic cables made of self-healing polyurethane material prepared in Examples 1-4 provided by the present invention have good bending performance and mechanical properties.
[0205] It can be seen from the test results of Example 1 and Comparative Examples 1 and 2 that when the hard segment content in the modified polyurethane is too high, it cannot provide excellent elasticity and flexibility, so that it can effectively absorb mechanical stress under repeated bending and torsion conditions, and the bending performance is insufficient; when the hard segment content is too low, the mechanical properties and heat resistance of the material decrease, and the stability decreases.
[0206] From the test results of Example 1 and Comparative Examples 3 and 4, it can be seen that an appropriate amount of carbon nanotubes can form a stress transfer network in the matrix, significantly improving the tensile resistance and fatigue resistance of the composite material. When the content is too high, the modified carbon nanotubes are unevenly dispersed and severely agglomerated, causing the material to become brittle and reduce flexibility; and if the addition amount is too low, the mechanical reinforcement effect is not obvious.
[0207] From the test results of Example 1 and Comparative Examples 5 and 6, it can be seen that an appropriate amount of modified boron nitride can improve the high and low temperature resistance and wear resistance of the material. When its content is too high, the material becomes brittle and its flexibility decreases; when its addition amount is too low, the thermal conductivity effect is not obvious and its high temperature resistance decreases.
[0208] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a robot joint dynamic cable using a self-repairing polyurethane material, characterized in that: The preparation method comprises: S1: After vacuum drying, polytetrahydrofuran diol is added to a reactor, and hexamethylene diisocyanate is added, and the reaction is carried out under nitrogen protection to obtain a reaction solution A; after cooling, 1,4-butanediol and dopamine hydrochloride are added to obtain a reaction solution B, and after heating, the reaction is carried out to obtain a reaction solution C; after adding dibutyltin dilaurate, the reaction is continued and vacuum degassing is carried out, and after completion, the product is purified to obtain a modified polyurethane; S2: placing carbon nanotubes in a plasma treatment chamber, introducing an Ar / O2 mixed gas for plasma treatment to obtain first modified carbon nanotubes, dispersing the first modified carbon nanotubes in anhydrous ethanol, adding a silane coupling agent KH550, refluxing after ultrasonic treatment, filtering, washing with ethanol, and vacuum drying to obtain modified carbon nanotubes; S3: dispersing montmorillonite in deionized water and stirring to obtain a montmorillonite dispersion, adding octadecyltrimethylammonium bromide solution dropwise, continuing stirring, then adding polyethyleneimine solution to obtain a reaction solution D, performing ultrasonic treatment and stirring again, and finally centrifuging, washing and freeze-drying to obtain a modified montmorillonite; S4: dispersing boron nitride in toluene to obtain a boron nitride dispersion, adding glacial acetic acid to adjust the pH after ultrasonic dispersion, and then adding 3-glycidyloxypropyltrimethoxysilane to obtain a reaction solution E, and refluxing under nitrogen protection; collecting by centrifugation, washing with anhydrous ethanol, and vacuum drying to obtain a first modified boron nitride; dispersing the first modified boron nitride in Tris buffer and adding dopamine hydrochloride, stirring at room temperature; centrifuging, washing, and freeze-drying to obtain a modified boron nitride; S5: placing the modified polyurethane in an internal mixer, adding an antioxidant, a dispersant, and a toughening agent, and sequentially adding modified carbon nanotubes, modified montmorillonite, and modified boron nitride after internal mixing to obtain a mixed material, and obtaining a composite material after constant temperature mixing, and injecting the composite material into a single-screw extruder, and simultaneously feeding the conductor body, and coating the composite material on the surface of the conductor, and obtaining a robot joint dynamic cable using a self-healing polyurethane material after cooling; The molar ratio of the polytetrahydrofuran diol to hexamethylene diisocyanate is 0.35-0.45:1; The robot joint dynamic cable using the self-healing polyurethane material comprises the following components in parts by weight: 65-75 parts of modified polyurethane; 3-5 parts of modified carbon nanotubes; 8-12 parts of modified montmorillonite; 12-15 parts of modified boron nitride; 0.3-0.5 parts of antioxidant; 0.8-1.2 parts of dispersant; and 2-3 parts of toughening agent.
2. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S1: The temperature of the polytetrahydrofuran diol vacuum drying is 85-95° C.; The vacuum-drying time of polytetrahydrofuran diol is 3-4h; The reaction temperature under nitrogen protection is 85-95°C; The reaction time under nitrogen protection is 1.5-2.5h; The reaction solution A is cooled to 55-65°C.
3. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S1: The molar ratio of 1,4-butanediol to dopamine hydrochloride is 0.8-1.2:1; The molar ratio of the total amount of dopamine hydrochloride to hexamethylene diisocyanate is 0.25-0.35:1; The temperature of the reaction liquid B is 105-115°C; The temperature of the reaction solution B is raised for 3.5-4.5 hours. The feeding amount of dibutyltin dilaurate is 0.08-0.12wt.% of the reaction solution C; After the dibutyltin dilaurate is added, the reaction is continued for 30-40 minutes; The vacuum degassing time is 15-25min.
4. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S2: The gas for plasma treatment is an Ar / O2 mixed gas with a volume ratio of argon to oxygen of 3:1-5:1; The power of the plasma treatment is 75-85W; The plasma treatment time is 3-5min; The mass fraction of the first modified carbon nanotubes dispersed in anhydrous ethanol is 2-3wt.%; The added amount of the silane coupling agent KH550 is 15-25% of the mass of the carbon nanotubes.
5. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S2: The ultrasonic treatment time is 25-35min; The reflux temperature is 75-85°C; The reflux time is 3.5-4.5h; The vacuum drying temperature is 55-65°C; The vacuum drying time is 10-14h.
6. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S3: The mass fraction of the montmorillonite dispersed in deionized water is 2.5-3.5wt.%; The stirring temperature after the montmorillonite is dispersed in deionized water is 25-35°C; The stirring time after the montmorillonite is dispersed in deionized water is 10-20 minutes; The mass fraction of the octadecyltrimethylammonium bromide solution is 4-6wt.%; The amount of octadecyltrimethylammonium bromide solution added is 25-35% of the mass of montmorillonite; The continued stirring time is 3.5-4.5h.
7. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S3: The amount of polyethyleneimine added is 15-25% of the mass of montmorillonite; The mass fraction of the polyethyleneimine solution is 1.5-2.5wt.%; The power of the ultrasonic treatment of the reaction solution D is 250-350W; The ultrasonic treatment time of the reaction solution D is 25-35 minutes; The temperature of the reaction solution D after ultrasonication and stirring is 65-75°C; The stirring time of the reaction solution D after ultrasonication is 5.5-6.5h; The freeze drying time is 20-28h.
8. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S4: The mass fraction of the boron nitride in toluene is 3.5-4.5wt.%; The ultrasonic dispersion time of the boron nitride dispersion is 15-20 minutes; After ultrasonic dispersion of the boron nitride dispersion, glacial acetic acid is used to adjust the pH to 4-5; The feeding amount of the 3-glycidyloxypropyltrimethoxysilane is 12-18% of the mass of the boron nitride; The reflux temperature of the reaction solution E under nitrogen protection is 70-80°C; The reaction solution E is refluxed under nitrogen protection for 6-8 hours; The vacuum drying temperature is 60-70°C; The vacuum drying time is 8-12h; The pH value of the Tris buffer is 8.3-8.7; The mass fraction of the first modified boron nitride in the buffer solution is 3.0-4.0wt.%; The amount of dopamine hydrochloride added is 10-15% of the mass of the first modified boron nitride; The stirring time at room temperature is 20-24h; The freeze drying time is 18-24h.
9. The method for preparing a robot joint dynamic cable using a self-repairing polyurethane material according to claim 1, characterized in that: In S5: The antioxidant is any one of antioxidant 1010, antioxidant 1076 or antioxidant 245, or a combination of at least two thereof; The dispersant is DISPERBYK-2150 or BYK-9077; The toughening agent is Kraton G1651 or Kraton FG1901; The temperature of the banburying is 180-190°C; The mixing time is 8-12 minutes; The temperature of the mixed material constant temperature kneading is 190-200°C; The mixing time of the mixed material at constant temperature is 10-20 minutes; The temperature of the single screw extruder barrel is 185-195°C.
10. A robot joint dynamic cable made of self-repairing polyurethane material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The robot joint dynamic cable using self-repairing polyurethane material comprises the following components in parts by weight: Modified polyurethane 65-75 parts; 3-5 parts of modified carbon nanotubes; 8-12 parts of modified montmorillonite; 12-15 parts of modified boron nitride; Antioxidant 0.3-0.5 parts; Dispersant 0.8-1.2 parts; 2-3 parts of toughening agent.
Citation Information
Patent Citations
Preparation of functionalized carbon nano-tube modification polyurethane elastomer
CN101440208A
Continuous carbon nano tube fiber-reinforced PA6 thermoplastic composite material and preparation method thereof
CN106987118A